Design of Potent Mannose-6-Phosphate Derivatives as Ligands for CI-M6P/IGF2R Using Fluorescence Polarization Assay - Mrázková, Lucie; Hladoníková, Klaudia; Toncarová, Barbora; Fischer, Michal; Zýka, Jakub; Kozák, Jaroslav; Kráľ, Michal; Kožíšek, Milan; Jiráček, Jiří; Kaminský, Jakub; Parkan, Kamil; Žáková, Lenka (Chemistry (Weinheim an der Bergstrasse, Germany), 2025)
The cation-independent mannose-6-phosphate/IGF2 receptor (CI-M6P/IGF2R) plays a crucial role in transporting lysosomal enzymes and other ligands. In this study, we designed and synthesized novel stable mannose-6-phosphate (M6P) derivatives to enhance their affinity for CI-M6P/IGF2R. To evaluate the binding potency, we employed a sensitive and cost-effective fluorescence polarization assay, enabling rapid quantification of receptor-ligand interactions in solution. The tested compounds included di-, tri-, and penta-M6P peptides along with various M6P-derived small molecules featuring phosphate isosteres or other functional modifications. Our findings indicate that ligands bearing multiple M6P moieties exhibit significantly higher receptor affinities than monomeric compounds and that phosphonate groups may serve as a more stable and potent alternative to native M6P. Computational modeling of ligand interactions with the CI-M6P/IGF2R domains further elucidated the binding mechanisms, offering new directions for the development of more effective ligands. This study advances the design of therapeutic strategies that leverage CI-M6P/IGF2R for targeted biomolecule delivery to lysosomes, thereby opening new possibilities for biomedical applications.
Keywords: vazba proteinů; Receptor, IGF Type 2; IGF2; Mannosephosphates; Ligands; lyzozomy; Humans; fluorescence polarization assay; Mannose‐6‐phosphate; Fluorescence Polarization; fluorescenční polarizace; ligand binding; Protein Binding; receptor; Drug Design; mannosafosfáty; receptor IGF typ 2; lidé; racionální návrh léčiv; ligandy; Lysosomes